Acquisition of the Conjugative Virulence Plasmid From a CG23 Hypervirulent Klebsiella pneumoniae Strain Enhances Bacterial Virulence - Tian, Dongxing; Wang, Weiwen; Li, Meng; Chen, Wenjie; Zhou, Ying; Huang, Yunkun; Sheng, Zike; Jiang, Xiaofei (Frontiers in Cellular and Infection Microbiology, 2021)
The emergence of hypervirulent and carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) has become a hot topic and confounding problem for clinicians and researchers alike. Conjugative virulence plasmids have the potential to cause more threatening dissemination of hv-CRKP strains. We previously identified K2606, a CG23 clinical hypervirulent strain of Klebsiella pneumoniae harboring a conjugative virulence plasmid designated pK2606. In this study we examined hypervirulence levels using assays of biofilm formation, serum resistance, and wax larvae and mouse in vivo infection models. Moreover, to define the transfer ability of pK2606 and whether this confers hypervirulence to other strains we performed plasmid transconjugation experiments between K2606 and the ST11 CRKP strain HS11286 along with E. coli J53. We found that although biofilm formation and serum resistance were not significantly increased, the transconjugants acquired the ability of produce high level of siderophores and also caused high mortality of wax larvae and mice. Furthermore, we identified pK2606-like conjugative virulence plasmids in GenBank, providing evidence that such plasmids may have begun to spread throughout China. These findings provide an evidence base for the possible mechanisms of the emergence of hv-CRKP strains and highlight the potential of pK2606-like conjugative virulence plasmids to spread worldwide.